Enterprise Reform and China’s Modernization - Li, Jiangjun; Han, Shengyue; Liang, Rui (Journal of Applied Business and Economics, 2022)
In China’s modernization, enterprises have experienced a complex process of change, which has promoted or restricted the process of China’s modernization. From the perspective of government function adjustment; this chapter studies the enterprise transformation process in China’s modernization from a historical perspective. It is found that although micro problems such as corporate governance and principal-agent are very important, they are only the second problem. The first problem should be the adjustment of government functions. The transformation practice of western countries has also proved the importance of flexible adjustment of government functions. In China, during the imperial period, enterprises in modern China did not develop due to the failure of government function adjustment. Thus, to catch up with and surpass the world powers, the new China after 1949 adopted a planned economic system, which is reasonable in the path. The Chinese government carried out the social transformation of market economy orientation after 1979. From then, the enterprises have become modern enterprises in the market economy. The findings of this chapter are of great significance to enhance the institutional innovation of enterprises and promote the process of China’s modernization.